Training loads and microcycle periodisation in Italian Serie A youth soccer players - Franceschi, A.; Robinson, M. A.; Owens, D. J.; Brownlee, T.; Bampouras, T. M.; Ferrari Bravo, D.; Enright, K. (Journal of Sports Sciences, 2024)
Microcycles are fundamental structures for training prescription and load management, helping to optimise training effects and performance. This study quantified external and internal loads of Italian Serie A youth soccer players across competitive weeks and their periodisation within microcycles. Data were collected from 90 players belonging to four age groups (under-19, -17, -16, -15) across a season. Methods of monitoring external [duration and global navigation satellite systems (GNSS)] and internal load [heart rate (HR) and rating of perceived exertion (RPE)] were employed. Linear mixed models determined differences in training loads across age groups, training days and player positions. Under-19 and under-17 players trained five times per week, while younger players trained four times. Late-stage academy players (under-19 and -17) demonstrated higher weekly accumulated external and sRPE training load compared to their younger counterparts (p < 0.05 between groups). Weekly accumulated HR internal loads were higher in under-15 players (p < 0.05 between groups). Marked fluctuations of daily load were observed across microcycles in under-19 and under-17 groups (p < 0.05 between days). These findings highlight progressive increases in training load throughout the development pathway, with late-stage academy players training with higher frequency, volume and marked periodisation compared to younger players.